2011
DOI: 10.1123/ssj.28.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Spatialities of Anger: Emotional Geographies in a Boxing Program for Survivors of Violence

Abstract: The primary aim of this article is to begin to articulate the spatiality and sociality of emotion in an action research project called Shape Your Life, a project designed to teach recreational boxing to female and transgendered survivors of violence in Toronto. In particular, the article is a theoretical and empirical examination of anger, the dominant emotional response to injustice. A case is made for a spatially engaged approach to the study of anger as a politically meaningful response to violence and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…As a result, various NGOs and practitioners attempted to develop SGD programs that use combative sports, such as boxing and martial arts, in combination with SRHR education campaigns and GBV-prevention strategies in order to empower women and girls with the knowledge and skills to feel safe [62]. Similarly, researchers have examined how self-defence sports are useful tools for empowering girls and women who have experienced violence in the global North countries [63][64][65][66][67]. These studies demonstrated that these initiatives enable the participants to actively negotiate and navigate aggression and violence in relation to their experiences with trauma.…”
Section: Connecting Gender-based Violence Sexual and Reproductive Hementioning
confidence: 99%
“…As a result, various NGOs and practitioners attempted to develop SGD programs that use combative sports, such as boxing and martial arts, in combination with SRHR education campaigns and GBV-prevention strategies in order to empower women and girls with the knowledge and skills to feel safe [62]. Similarly, researchers have examined how self-defence sports are useful tools for empowering girls and women who have experienced violence in the global North countries [63][64][65][66][67]. These studies demonstrated that these initiatives enable the participants to actively negotiate and navigate aggression and violence in relation to their experiences with trauma.…”
Section: Connecting Gender-based Violence Sexual and Reproductive Hementioning
confidence: 99%
“…In total, 16 1 studies met the inclusion criteria and were critically analyzed using the meta-study methodology presented above. Ten studies examined the impacts of various interventions, which included boxing (van Ingen, 2011, 2016); the use of sport within a disarmament, demobilization, and reintegration camp for ex-combatants (Dyck, 2011); a sport and mental health intervention for a traumatized refugee from a war-torn country (Ley, Rato Barrio, & Koch, 2018); yoga (Rhodes, 2015); a sports-based youth development program for refugees (Whitley, Coble, & Jewell, 2016); and prison-based sport and fitness programs for youth offenders (Andrews & Andrews, 2003; Meek & Lewis, 2014; Parker, Meek, & Lewis, 2014; Van Hout & Phelan, 2014). The remaining six articles explored the role of sporting activities in naturalistic settings.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining six articles explored the role of sporting activities in naturalistic settings. Seven studies were conducted with individuals who had experienced trauma (Ley et al, 2018; Massey & Whitley, 2016; Ratcliff, Farnworth, & Lentin, 2002; Rhodes, 2015; van Ingen, 2011, 2016; Whitley, Massey, & Wilkison, 2016); five studies included participants who had been displaced, had been exposed in warfare, or were in potentially traumatizing events such as natural disasters or extreme community violence (Dyck, 2011; Sobotova, Safarikova, & Gonzalez Martinex, 2016; Spaaij, 2015; Thorpe, 2016; Whitley, Coble, & Jewell, 2016); and four studies were specific to youth who had disruptions in caregiving as evidence by their placement in the criminal justice systems (Andrews & Andrews, 2003; Meek & Lewis, 2014; Parker et al, 2014; Van Hout & Phelan, 2014). Overall, differences in theoretical and methodological approaches emerged across (and to a smaller degree within) these groupings and are discussed in further detail below.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations